Role of Women in Poultry Rearing Amongst Resource-poor Mixed Farming Families - M. L. Roy and K. S. Kadian, (Indian Journal of Extension Education, 2013)
The present study was conducted in all the six agro-climatic zones of West Bengal. Two blocks were selected randomlyfrom each agro-climatic zone. One village from each block was selected randomly. A total of 61 poultry rearing farmhouseholds were selected randomly from 12 villages. Husband and wife of each selected farm household were taken asrespondents which constituted a total sample size of 122 respondents. The poultry unit possessed by farm families wasobserved generally having an average of 6-7 adult birds. It was found that all the poultry related daily activities werepredominantly performed by farm wives. Their highest participation was recorded in the activity of collection and storageof eggs (88.52%) followed by feeding and watering of birds (86.89%) and lowest involvement was observed in watchingof birds (62.30%). Husbands' participation varied from zero per cent (in case of feeding and watering) to 27.87 per cent (incase of watching of birds). Husband-wife joint participation was found almost negligible. Family members' involvementin poultry related daily activities varied from 1.64 per cent (collection and storage of eggs) to 11.48-19.67 per cent(cleaning of poultry house). It was reported that husbands were predominantly involved in purchasing of poultry feed(63.93%) and other two occasional activities like hatching activity and selling of eggs and birds were mostly taken care byfarm wives (88.52% and 50.82% respectively). It was found that on an average a farm family keeping an average of 6-7adult birds spent 62.37 minutes per day in poultry related daily activities and 4 man-days/annum in occasional activities,in which 86.08 per cent of total time in daily activities and 75 per cent of total time in occasional activities were spent byfarm wives.